E-Modul Kesehatan Sekolah Berbasis Pop-Up Story Animation terhadap Sikap Peduli Kesehatan Siswa SD di Daerah Tertinggal - Septi Aprillia; Dian Permatasari Kusuma Dayu (Universitas Muhammadiyah Mataram, 2026)
Abstract: The low level of health awareness attitudes among elementary school students in underdeveloped areas has become a critical issue affecting the implementation of clean and healthy living behaviours in school environments. Limited availability of engaging and contextual learning media has resulted in suboptimal health education practices. This study aimed to examine the effect of a Pop-Up Story Animation–Based School Health E-Module on the health awareness attitudes of elementary school students in underdeveloped areas. The research employed a quantitative method with a quasi-experimental design. The research subjects consisted of 60 fifth-grade students, divided into an experimental group and a control group. Data were collected through health awareness attitude questionnaires, observations, and documentation. The collected data were analysed using descriptive and inferential statistical techniques, including normality tests, homogeneity tests, and an independent sample t-test. The results revealed a significant difference in students’ health awareness attitudes between the group taught using the Pop-Up Story Animation–Based E-Module and the group receiving conventional instruction. Therefore, it can be concluded that the Pop-Up Story Animation–Based School Health E-Module is effective in improving the health awareness attitudes of elementary school students in underdeveloped areas. These findings imply that the integration of interactive digital learning media can serve as an innovative solution to enhance the quality of health education in elementary schools, particularly in underdeveloped regions.Abstrak: Rendahnya sikap peduli kesehatan siswa sekolah dasar di daerah tertinggal menjadi permasalahan yang berdampak pada perilaku hidup bersih dan sehat di lingkungan sekolah. Keterbatasan media pembelajaran yang menarik dan kontekstual menyebabkan pembelajaran kesehatan belum berjalan secara optimal. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan E-Modul Kesehatan Sekolah berbasis Pop-Up Story Animation terhadap sikap peduli kesehatan siswa sekolah dasar di daerah tertinggal. Penelitian ini menggunakan metode kuantitatif dengan desain quasi-eksperimental. Subjek penelitian berjumlah 60 siswa kelas V, yang terdiri atas kelas eksperimen dan kelas kontrol. Teknik pengumpulan data dilakukan melalui angket sikap peduli kesehatan, observasi, dan dokumentasi. Data yang diperoleh dianalisis menggunakan statistik deskriptif dan inferensial, meliputi uji normalitas, uji homogenitas, dan uji t (independent sample t-test). Hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan pada sikap peduli kesehatan siswa antara kelas yang menggunakan e-modul berbasis Pop-Up Story Animation dan kelas yang menggunakan pembelajaran konvensional. Dengan demikian, dapat disimpulkan bahwa E-Modul Kesehatan Sekolah berbasis Pop-Up Story Animation efektif dalam meningkatkan sikap peduli kesehatan siswa sekolah dasar di daerah tertinggal. Penelitian ini memberikan implikasi bahwa pemanfaatan media digital interaktif dapat menjadi solusi inovatif untuk meningkatkan kualitas pendidikan kesehatan di sekolah dasar, khususnya di wilayah tertinggal.